2003
DOI: 10.1007/s00134-002-1560-7
|View full text |Cite
|
Sign up to set email alerts
|

Neutropenia and the development of the systemic inflammatory response syndrome

Abstract: Mortality and progression to septic shock increased as more SIRS criteria were met on admission. SIRS stages could serve as a risk-assessing model in febrile neutropenic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 9 publications
1
13
1
Order By: Relevance
“…The number of neutropenic patients in this study was only 5, with 1 death in ICU. Despite the limited number of patients, these data coincide with those observed by Regazzoni et al [34], Póvoa et al [35], and Souza-Dantas et al [21], which found no association between neutropenia and mortality in cancer patients.…”
Section: Discussionsupporting
confidence: 88%
“…The number of neutropenic patients in this study was only 5, with 1 death in ICU. Despite the limited number of patients, these data coincide with those observed by Regazzoni et al [34], Póvoa et al [35], and Souza-Dantas et al [21], which found no association between neutropenia and mortality in cancer patients.…”
Section: Discussionsupporting
confidence: 88%
“…[17][18][19][20][21][22][23][24] Previously published data on the test characteristics of SIRS have largely focused on the SIRS score at the time of presentation to the emergency department or upon admission to the medical floor or ICU. Since our patients are often admitted for prolonged hospital stays (30 day planned admissions) …”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that some basic studies found similar profiles of inflammatory mediators in septic patients independently of whether they had neutropenia or not [5]. Inflammation-mediated processes such as SIRS [25] and the ARDS [15,22] also occur in neutropenic patients. Our results, therefore, strengthen those partial descriptions, in showing a similar clinical evolution of septic shock in terms of mortality and number of organ failures, despite a low white cell count.…”
Section: Or Bonementioning
confidence: 90%
“…The data available at present, however, point to the similarities of the profiles of inflammatory mediators in septic patients with and without neutropenia [12,21]. In contrast, clinical descriptions of the manifestations of SIRS among neutropenic patients with cancer are scarce and controversial [15,22,25]. Some studies have focused on neutropenic critically ill cancer patients [3,4,8,11,15,22,25], but they do not clarify whether there are additional implications for neutropenia when septic shock ensues, and there is no consistent view as to its repercussions on overall ICU survival [14,28].…”
Section: Introductionmentioning
confidence: 94%